Constraining Ideas: How Seeing Ideas of Others Harms Creativity in Open Innovation. (February 2021) - Hofstetter, Reto; Dahl, Darren W.; Aryobsei, Suleiman; Herrmann, Andreas
Open innovation contests that display all submitted ideas to participants are a popular way for firms to generate ideas. In such contest-based ideation, the authors show that seeing numerous competitive ideas of others harms, rather than stimulates, creative performance (Study 1). Others' competitive prior ideas interfere with idea generation, as new ideas need to be differentiated from the preceding ones to be original. Exposure to an increasing number of prior ideas thus heightens individuals' perceived constraints of expressing ideas and harms creative performance (Studies 2 and 3). Furthermore, creative performance monotonically reduces with an increasing number of prior ideas (Study 4). A final study demonstrates that showing only a limited number of ideas as well as grouping prior ideas offer actionable ways to reduce prior ideas' harmful influence (Study 5). These results illustrate viable ways to improve contest-based ideation outcomes merely by changing how competitive prior ideas are presented.